2019
DOI: 10.1002/jmv.25577
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin, an intracellular marker for HIV‐associated CD4 T‐cell motility dysregulation, shed light on the mechanisms of incomplete immune reconstitution in the patients with HIV

Abstract: Highlights People living with HIV do not achieve an optional immune reconstitution despite the sustained virologic suppression. Circulating CD4 T cells fail to replenish their lymphoid tissue counterparts in people living with HIV. Irrespective of ART, coffin hyperactivation and impaired T cell mobility persist in people living with HIV. Cofilin may represent a novel therapeutic target to restore T cell mobility in people living with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 10 publications
2
91
0
Order By: Relevance
“…Epidemiologic measurements have been explored to identify the dynamics of disease regarding the spread risk and the effect of human mobility [3][4][5][6][7][8][9][10]. Besides, since the mobility restrictions are considered as a critical factor to prevent the disease spread, studies have assessed its impact [11][12][13][14][15][16]. Non-pharmaceutical observations are also proven to be effective data sources to have an integrated perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic measurements have been explored to identify the dynamics of disease regarding the spread risk and the effect of human mobility [3][4][5][6][7][8][9][10]. Besides, since the mobility restrictions are considered as a critical factor to prevent the disease spread, studies have assessed its impact [11][12][13][14][15][16]. Non-pharmaceutical observations are also proven to be effective data sources to have an integrated perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Priya and Shanker ( Priya & Shanker, 2020 ) have observed that the coevolutionary forces can increase the fitness of spike glycoprotein against ACE2 and increase the infectivity of SARS-CoV-2. According to Uddin et al ( Uddin et al, 2020 ) antigenic epitopes of SARS-CoV-2 and SARS-CoV have highest level of similarities among them.SARS-CoV-2 is the seventh coronavirus to infect humans but the first HCoV which pandemic potential ( Seyran et al, 2020 ). (Accession no: NC _045512) is the first SARS-CoV-2 sample SARS-CoV-2 sequence from Wuhan, and it is from clade’O′(Others) ( Mercatelli & Giorgi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to CRF60_BC, the subtype C parental strain of CRF108_BC is phylogenetically related to the subtype C strain circulating in Brazil. However, the recombination event giving rise to CRF108_BC could have occurred either in Brazil, where both B and C subtypes co-circulate at high proportions in some areas [ 42 , 43 ] or in Spain, since we could not track the ancestry of the parental subtype B strain to any country. A Spanish origin of CRF108_BC would be supported by an inferred Spanish tMRCA in the city of Vitoria, Basque Country, Northern Spain, around 2000.…”
Section: Discussionmentioning
confidence: 99%